Insulin receptor and insulin resistance in type -2 diabetes - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
Resistance to the glucoregulatory effects of insulin is well-documented in type -2, non-insulindependent diabetes. Two separate factors may contribute in the pathogenesis, namely the obesity-related and the non-obesity-related.Obesity-related insulin resistance is associated with hyperinsulinemia, reduced numbers of insulin receptors on target cells. The mechanism by which the insulin receptor number is decreaSed is not clearly understood. This phenomenon is called